MEDIATING PERCEIVED ENJOYMENT IN INFLUENCING ONLINE IMPULSE BUYING: STUDY OF STIMULUS ORGANISM RESPONDE (S-O-R) THEORY - Yazida Salsa Biila; M Alfan Hadiar Dhofir (UIN Raden Mas Said Surakarta, 2024)
This research aims to analyze the influence of intensity of use of Instagram social media, content affiliate marketing and lifestyle compatibility on online impulse buying mediated by perceived enjoyment among students in Surakarta. Using a sample of 285 respondents, this research applied a cluster sampling technique, meaning that there was representation from each district of Klaten, Sragen, Boyolali, Sukoharjo, Surakarta, Karanganyar, and Wonogiri. The data were processed by using SmartPLS 3. The results indicate that the direct influence of intensity of use of social media Instagram and lifestyle compatibility on online impulse buying is not significant. Content affiliate marketing has a significant influence on online impulse buying, both directly and indirectly. Perceived enjoyment influences online impulse buying, while also being able to mediate all influences, either partially or fully mediated. This research succeeded in proving the role of the S-O-R theory in influencing online impulse buying. Lifestyle compatibility tends to play the biggest role in increasing positive emotions in the form of perceived enjoyment and has a significant impact on online impulse buying.